The Effect of Social Support on Academic Resilinece to Student Who Are Working on Thesis - Putri Auliah Nur Efendi; Hilwa Anwar; Nur Akmal (PT ARRUS Intelektual Indonesia, 2023)
Academic resilience is an individual's ability to survive, rise, and adapt to difficult and stressful conditions in the academic field. This study aims to determine the effect of social support on resilience in final students who are working on their thesis. The research subjects were final year students of the 2016-2019 class who were working on their thesis, totaling 210 students. The sampling technique used is accidental sampling. The measuring instrument for the academic resilience scale is the scale compiled by Cassidy (2016), while the social support scale is the scale compiled by Zimet (2010). The results of hypothesis testing in this study used a simple linear regression test with the result r = 0.262 with p = 0.000. These results indicate that there is a significant positive effect of social support on academic resilience in final students who are working on their thesis. The implication of this research is that final students are expected to be able to maintain their academic resilience, one of which is by increasing individual attachment and good communication with those around them.